2017
DOI: 10.1161/jaha.116.005288
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐Five‐Year Alcohol Consumption Trajectories and Their Association With Arterial Aging: A Prospective Cohort Study

Abstract: Background--Emerging evidence suggests that arterial stiffness, an important marker of cardiovascular health, is associated with alcohol consumption. However, the role of longer-term consumption patterns in the progression of arterial stiffness over time remains unclear. A longitudinal cohort design was used to evaluate the association between alcohol consumption over 25 years and subsequent changes in arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 50 publications
4
50
0
4
Order By: Relevance
“…Although the number and frequency of repeated measures reported by existing studies are variable, and no study is yet to capture drinking behaviours throughout the whole adult life‐course , the use of repeated measures is important if differences in risk between heterogeneous consumption trajectories are to be understood more clearly and sensitive periods identified during which particular alcohol consumption behaviours may be most harmful, aiding the targeting of alcohol reduction interventions . To date, however, there is no consistent approach to handling such data, with some opting to restrict analyses to participant whose consumption was stable within pre‐defined limits , or else categorizing participants according to whether their drinking increased, decreased or remained stable over a given period of time . In addition, there is no clear agreement concerning the appropriate means of classifying drinkers who cease consumption prior to baseline measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number and frequency of repeated measures reported by existing studies are variable, and no study is yet to capture drinking behaviours throughout the whole adult life‐course , the use of repeated measures is important if differences in risk between heterogeneous consumption trajectories are to be understood more clearly and sensitive periods identified during which particular alcohol consumption behaviours may be most harmful, aiding the targeting of alcohol reduction interventions . To date, however, there is no consistent approach to handling such data, with some opting to restrict analyses to participant whose consumption was stable within pre‐defined limits , or else categorizing participants according to whether their drinking increased, decreased or remained stable over a given period of time . In addition, there is no clear agreement concerning the appropriate means of classifying drinkers who cease consumption prior to baseline measurement.…”
Section: Discussionmentioning
confidence: 99%
“…(Sookoian et al, 2016) We found that, among women, the risks associated with heavy drinking in mid-life were only appreciable when considering a longitudinal drinking typology and not in cross-sectional analyses. This further emphasises the necessity of taking a life course approach when assessing the association between alcohol consumption and health outcomes (Bell and Britton, 2015b;O'Neill et al, 2017). There is a serious risk of misclassification if only one measure of alcohol is considered.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, the importance of lifestyle modification irrespective of pharmacological treatment has been emphasized, particularly for diabetes mellitus given a lack of evidence that glycemic control alone improves macrovascular outcomes . Last, though low or moderate alcohol consumption has been associated with cardiovascular benefits, the link is complicated and the benefits of alcohol are offset by its well‐known potential harms, which may affect its perceived health impact. Differing interpretations or estimations of this balance of risk and benefit may account for the negative association between abstinence from alcohol and PNIPH as well as for the lack of association between excessive alcohol consumption and PNIPH.…”
Section: Discussionmentioning
confidence: 99%